ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN MUARA ENIM - Anna Yulianita (Jurnal Ekonomi Pembangunan, 2010)
This study entitled Analysis of Main Economic Sectors in Muara Enim regency. The purpose of this research is to identify the sectors untuak seeded anything that can be developed in the economy in the Muara Enim regency period from 2001 until 2008. Data used in this research is secondary data derived from various sources. This research was shaped desriptif and uses quantitative techniques desriptif. Quantitative analysis using the calculation technique Location Quotient (LQ) and shift share analysis. The result shows that (1) there is one sector and the three sub-sectors that can be used as the mainstay of superior, as indicated by an LQ> 1 namely the Mining Sector and the results, sub-sectors of Food Crops, Forestry sub-sector sub-sector of Electricity, Rail Transportation subsector. (2) the shift share analysis there are four leading sectors namely Agriculture sector, Mining sector and results, Manufacturing Industry sector and building sector, which is positive. Figures elasticity of 5.64, this means that every change of one percent on the real sector, the service sector will increase by 5.64 percent. It is expected that all these leading sectors to balance the economic growth of the Muara Enim regency. Keywords: Competitive Sector, Location Quotient, Shift Share, Elasticity, Muara Enim